2002
DOI: 10.1046/j.1365-2141.2003.03979.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional deficiencies of leukaemic dendritic cells from patients with chronic myeloid leukaemia

Abstract: Summary. Chronic myeloid leukaemia (CML) dendritic cells (DC) are possible candidates for inducing antileukaemic immunity. This study aimed to investigate the frequency, phenotype and function of blood-derived leukaemic DC in comparison with DC from healthy donors using flow cytometric assays and mixed leucocyte reaction (MLR). Immature leukaemic DC displayed a reduced endocytotic capacity as compared with healthy controls. Moreover, in vitro maturation of leukaemic DC was found to be deficient. Expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…DCs display impaired maturation in response to LPS and PGE 2 treatment and impaired migration as compared to monocyte-derived DCs. 8 Fortunately, our data showed no significant functional defects in AML-derived APCs with respect to maturation and migration as compared to normal CD34 þ cell-derived DCs.…”
Section: To the Editormentioning
confidence: 86%
“…DCs display impaired maturation in response to LPS and PGE 2 treatment and impaired migration as compared to monocyte-derived DCs. 8 Fortunately, our data showed no significant functional defects in AML-derived APCs with respect to maturation and migration as compared to normal CD34 þ cell-derived DCs.…”
Section: To the Editormentioning
confidence: 86%
“…Using the KEGG pathways to analyze targets of dysregulated miRNAs across the progression of CML, we have found that many dysregulated potential target molecules were involved in several biological pathways including metabolic and cancer pathways, the MAPK signaling pathway, endocytosis, cytokine-cytokine receptor interaction and focal adhesion. Recent studies have confirmed that pathogenesis and progression of CML were closely related to the MAPK signaling pathway [27,28], endocytosis [29,30] and focal adhesion [31,32].…”
Section: Oncotarget S474 Wwwimpactjournalscom/oncotargetmentioning
confidence: 97%
“…For use in immunotherapy, dendritic cells are generated and pulsed with tumor-specific antigens under in vitro conditions [2,3]. Usually, peripheral blood monocytes are used as DC precursors [4]. In patients with myeloid leukemias, dendritic cells (DC) may originate from leukemic cells and thus may also express leukemia-specific antigens.…”
Section: Introductionmentioning
confidence: 99%